INITIAL CLINICAL STAGING AND INCIDENCE OF MOLECULAR SUBTYPE IN BREAST CANCER PATIETS TREATED FROM JAN/2011 TO DEC/2019 AT PÉROLA BYINGTON HOSPITAL - Oliveira, Mauro Orlando Meurer; Shida, Jorge Yoshinori; Mattar, André; Cavagna, Felipe Andreotta; Gebrim, Luiz Henrique (Mastology, 2021)
Introduction: Clinical staging (CS) has great importance for therapeutic programming and prognostic evaluation in patients diagnosed with breast cancer. Malignant breast tumors can be classified according to their immunohistochemi- cal (IHC) profile. The study of the IHC profile can also assist in public health strategies, since they determine therapeutic planning. Objectives: Compare our database with literature data. Methods: The staging database (TNM, Tumor, Nodes and Metastasis) of the CRSM-SP (Pérola Byington Hospital) of patients with breast cancer treated at this institution from January 2010 to December 2019. Results:It was observed that 5.7% of the patients had in situ tumors. In the invasive form of tumors, 22.7% of the patients were diagnosed in CS I. Stage II was the one with the highest occurrence, corresponding to 36.5%. Advanced cases belonging to stages III and IV respectively represented 28.2% and 3.26%. As for the IHC profile of our 10,665 patients, luminal tumors A represented 24.7%, luminal B 32.7%. Patients with overexpressed HER2 were sub- divided into pure HER2 (7.7%) and triple positive (9.8%). Triple negative tumors represented 25.1% of patients. A Brazilian study with SUS (Brazilian Unified Health System) data included 201,079 women: 19.5% were in stage I, 40.4% in stage II, 30.9% in stage III, and 9.3% in stage IV. In comparison with the public health system in England, a population study of 86,852 cases of breast cancer found 37% of diagnoses in stage I, 32% in CS II, 8% in CS III, and 5% in CS IV. The high ratio of patients (17%) in an unknown staging is noteworthy. In the USA, in a population study of 320,124 women, 72.6% were classified as luminal A, 11.2% as luminal B, 4.8% with overexpression of HER2 and 11.3% as triple-negative. Data from a Brazilian publication with 2,461 patients observed luminal A in 28.8% of the cases, luminal B 39.5%, pure HER2 7.9%, tri- ple positive 9.7% and triple-negative were 14%, with the exception of triple-negative, similar to our results. It is possible that the higher ratio of patients with triple negative tumors at CRSM is explained by the higher incidence of non-screened patients, aged under 50, which are about 39%. Conclusions: The finding of 28.4% of in situ tumors in stage I shows the results of an occasional screening. The predominance of patients in stage II (40.4%) shows the predominance of palpable tumors in our population and the importance of making an agile diagnosis, preventing progression to stage III. The pre- dominance of luminal tumors 68.3% and HER 2 (16.7%) were similar to those in the literature. However, the ratio of 25.1% of triple-negative patients contributes to higher mortality in Brazil and requires greater diagnostic and therapeutic agility